Analysis of Students' Preparednes In Public and Private High School Students For Landslide Disaster Risk In Maja District - Arie Ramadhan Pribudianto; Enok Maryani; Darsiharjo Darsiharjo (Universitas Pendidikan Indonesia, 2023)
Disasters are the result of natural and social processes. The natural condition of an area has the potential for danger; it can appear as a natural disaster. Efforts to reduce disaster risk can be done by changing human behavior and increasing awareness and concern for preserving the environment. Changing human behavior can be done by changing the mindset and getting used to it from an early age to always care about the environment and be aware of disasters. Through disaster education in schools, it is hoped that it will be able to increase disaster preparedness. Maja District, which is in Majalengka Regency, is one of the areas that has a high risk of landslides, which can pose a hazard if the community and students around the area have low disaster preparedness. The purpose of this study was to find out how big the risk of landslides is in Maja District and to see the level of preparedness of high school students in facing the risk of landslides. The population in this study were all high school students in Maja District. The method used by researchers is a survey research method with descriptive analysis. While this research approach, uses a quantitative approach. In 2017, Maja District had 7 cases of landslides, which is the second most-cases number in Majalengka Regency. Given the large potential for landslides, the local government should have implemented an optimal disaster mitigation process as stated in Law Number 24 of 2007 concerning Disaster Management.Keywords: Student Preparedness, Disaster Risk, Landslide Disaster, Maja District